Nelson : love & fame - Vincent, Edgar (Yale University Press, 2003)
The story of Horatio Nelson's life - his naval glory, public fame, charismatic leadership, scandalous romance, and untimely death as he led the British to victory at the Battle of Trafalgar. This biography of Nelson (1758-1805) presents an account of his climb to fame as well as the details of his personal and emotional life. A man of contradictions, Nelson emerges in this biography as a ruthless and aggressive leader, the epitome of a fighting commander; an ambitious attention-seeker capable of self-pity, self-delusion and childish behaviour; yet to be admired for his transcendent courage, kindness and leadership skills, which inspired love and affection in those he led. Edgar Vincent builds on research and examines the extensive primary sources, seeking to enlarge our understanding of Nelson the man. He offers interpretations of Nelson's victories to illustrate his grasp of today's concept of mission-command two centuries ahead of his time; his disobedience of his Commander-in-Chief's orders; and his part in the bloody and chaotic Napoleonic counter-revolution. Vincent also analyses the motives and attitudes of key figures who surrounded him, among them Earl Spencer, Earl St Vincent, Sir William Hamilton and Thomas Troubridge. Interwoven with the events of Nelson's career is his emotional journey, his early infatuations, his courtship and marriage with Frances Nisbet, and his all-consuming affair with his mistress Lady Hamilton, one of the most celebrated beauties of the 18th century and the mother of his child.